The Use of The K-W-D-L Technique in the Development of Grade 10 Students’ Mathematical Problem-Solving Abilities - Nantawat Sawatpon; Titiworada Polyiem (Journal of Educational Issues, 2024)
The purposes of the study were to investigate the effectiveness of the K-W-D-L technique on grade 10 students’ mathematical problem-solving abilities and to study the students’ attitudes toward learning mathematics after participating in learning management designed using the K-W-D-L technique. The participants were 40 grade 10 students in a public school in Thailand selected using a purposive sampling method. The instruments were learning management designed using the K-W-D-L technique to teach the fundamental concept of counting in mathematics class, a mathematic problem-solving test, and an attitude survey questionnaire. The data were analyzed using percentage, mean score, standard deviation, single sample t-test, and effectiveness index. The study’s findings indicate that the K-W-D-L learning management was effective in developing Thai participants’ mathematical problem-solving abilities and that the participants expressed satisfaction with the method. The study’s findings may have implications in both educational and academic settings.